1999
DOI: 10.1021/ef9802532
|View full text |Cite
|
Sign up to set email alerts
|

Chemical Structure and Biomarker Content of Jinghan Asphaltenes and Kerogens

Abstract: The compound classes and biomarker compositions of immature Jinghan crude oil asphaltenes and their potential respective source rock kerogens have been investigated by chemolysis. The C-S-, C-O-, and C arom -C-bound appendages have been liberated by Ni 2 B reduction, BBr 3 hydrolysis, and ruthenium-ions-catalyzed oxidation. Measured were the saturate, aromatic, and polar (+ asphaltene) compound classes and the homologous series of hydrocarbon biomarkers: n-alkanes, regular isoprenoids, steranes, 4-methylsteran… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
32
0
1

Year Published

2002
2002
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(35 citation statements)
references
References 18 publications
2
32
0
1
Order By: Relevance
“…Typically, asphaltenes were defined as the crude oil fractions that are insoluble in aliphatic solvents but soluble in aromatic solvents; thus, asphaltenes separated from crude oil by low molecular weight alkanes contain the most polar and the highest molecular weight species of crude oil (Chang and Fogler, 1994). Peng et al (1999) also indicated that low molecular weight asphaltenes usually comprise chemisorbed and coprecipitated resins along with low molecular weight asphaltene fragments. Since it may be difficult to completely ionize asphaltene fractions by ESI due to the wide molecular weight range, the species analyzed by FT-ICR MS may only account for lower molecular weight compounds in asphaltene fractions.…”
Section: Compound Class Distributionmentioning
confidence: 99%
“…Typically, asphaltenes were defined as the crude oil fractions that are insoluble in aliphatic solvents but soluble in aromatic solvents; thus, asphaltenes separated from crude oil by low molecular weight alkanes contain the most polar and the highest molecular weight species of crude oil (Chang and Fogler, 1994). Peng et al (1999) also indicated that low molecular weight asphaltenes usually comprise chemisorbed and coprecipitated resins along with low molecular weight asphaltene fragments. Since it may be difficult to completely ionize asphaltene fractions by ESI due to the wide molecular weight range, the species analyzed by FT-ICR MS may only account for lower molecular weight compounds in asphaltene fractions.…”
Section: Compound Class Distributionmentioning
confidence: 99%
“…Meanwhile the occluded hydrocarbons inside the asphaltenes were released, which can be distinguished from the adsorbed hydrocarbons obtained from the initial asphaltenes by acetone extracting (Liao et al, 2006b;). The hydrocarbons occluded inside the asphaltenes were well protected from secondary alterations in the reservoir due to the macromolecular structures of asphaltenes, therefore they retain the early generation information of crude oils (Behar et al, 1984;Ekweozor, 1984Ekweozor, , 1986Peng et al, 1997Peng et al, , 1999. Thus, the geochemical features of the compounds adsorbed and occluded inside asphaltenes can provide useful information concerning the charging or mixing processes of oils.…”
Section: Introductionmentioning
confidence: 98%
“…Sulphur atoms are essentially present in thiophene and organic sulphur [5][6][7]. However, the composition of asphaltenes depends upon the origin of crude oil and the method of extraction [8][9][10][11][12][13].…”
Section: Introductionmentioning
confidence: 99%